Pengaruh Penerapan Manajemen Risiko Bisnis dalam Small Business Development pada UMKM Board Games - Yuswardi Yuswardi; Febryna Adinda; Helen Helen; Lara Meilani; Valeska Lilya Kevin; Vallencia Vallencia (Jurnal Mirai Management, 2022)
Board Games Café is one of the Micro, Small and Medium Enterprises (MSMEs) engaged in the culinary field. This Board Games Café is a café that offers a variety of varied foods and drinks that can be chosen according to consumer tastes, and has many variations of games that can be played when visiting the Board Games Café. This study aims to determine what business risks occur in the Board Game Café. This research method is a purposive sampling method, which is the type of method used in the process of preparing this report. Purposive Sampling Technique is a sampling technique in qualitative research. The results of the study show that the risks faced by Board Game Café are risks posed by external factors such as Covid-19 that occurred in Batam in early 2020-2022. Losses in turnover caused by Covid-19 and damage to equipment caused by long usage and the risk of not having regular customers. This research simplifies and assists in dealing with risks in business. Keywords: Risk, Board Games Café, Business